A case report of arsenic-induced peripheral neuropathy misdiagnosed as Guillain-Barré syndrome - Fu, Shanshan; Wu, Guanao; Zhan, Yibo; Xia, Hui; Zhou, Chang; Zeng, Jingjing; Tang, Ye; Pan, Boyan; Zheng, Zequan; Zhao, Min; Zhao, Yuanqi; Xu, Haoyou (Frontiers in Toxicology, 2026)
ObjectiveTo explore the clinical characteristics and misdiagnosis causes of arsenic-induced peripheral neuropathy.MethodsWe report a case of arsenic-induced peripheral neuropathy initially misdiagnosed as Guillain-Barré syndrome, with analysis of clinical characteristics, diagnostic workup and therapeutic management, supplemented by literature review.ResultsA 58-year-old male presented with progressive peripheral neuropathy, initially diagnosed with Guillain-Barré syndrome but later suspected as chronic inflammatory demyelinating polyneuropathy. However, his symptoms progressed despite standard immunotherapy, developing generalized motor deficits, myokymia, ascending sensory loss, and facial palsy. Careful reevaluation revealed critical diagnostic clues: a history of intermittent topical application of an unidentified herbal medicine preceding symptom onset, accompanying gastrointestinal prodromal symptoms, and characteristic physical findings including Mee’s lines, lower limb hyperpigmentation, and foot hyperkeratosis. Subsequent laboratory testing confirmed markedly elevated arsenic levels in nail and hair samples, ultimately establishing the diagnosis of arsenic-induced peripheral neuropathy.ConclusionArsenic-induced peripheral neuropathy can clinically mimic Guillain-Barré syndrome. For immunotherapy-refractory cases, clinicians should maintain high suspicion for potential heavy metal poisoning. Careful elicitation of toxic exposure history and recognition of characteristic dermatologic findings are critical for definitive diagnosis, as early recognition significantly improves prognosis.